Quality of work life dan self-esteem pada kinerja karyawan - Anisya, Dina; Muttaqien, Zaenul; Dewi, Anita Sumelvia (Implementasi Manajemen & Kewirausahaan, 2022)
This study aimed to investigate the significance of the effect of quality of work life and self-esteem on employee performance. This study employed a quantitative research design. The research sample was 32 employees of PT. Podomoro Poultry Equipment. Data collection was done by distributing closed questionnaires; quality of work life questionnaire, self-esteem questionnaire, and employee performance questionnaire; using a Likert scale 1-5 which was given to respondents directly. The analysis phase was carried out the first time by testing the validity and reliability of the questionnaire. Data analysis was performed using multiple regression analysis with SPSS 25.0. The results of the study found that simultaneously, quality of work life and self-esteem had a significant effect on employee performance, and partially it was also found that quality of work life and self-esteem had a significant effect on employee performance.